Miconia amplipedunculata (Melastomataceae: Miconieae), a new species from the Caribbean lowlands of Panama - Almeda, Frank; Ortíz, Orlando O. (Phytotaxa, 2022)
Miconia amplipedunculata is described as a new species that is known from a limited area in the Caribbean lowland rainforests of Panama. Line drawings, field photographs, a distribution map, and a comparative discussion of morphologically similar species are provided. This species is readily distinguished by its short-petiolate alternately 3-plinerved leaf blades, brown amorphous stellulate-lepidote indumentum on the primary and secondary veins of abaxial foliar surfaces and inflorescence, long-pedunculate (up to 12.5 cm) inflorescence, persistent bracts and bracteoles, unlobed truncate calyx, prominent subulate calyx teeth that exceed the calyx, 5-merous flowers, distally constricted anther filaments, and isometric and isomorphic stamens that lack appendages. The new species is compared with M. iteophylla, M. jefensis, M. ligulata, and M. peltata. All of these species, except M. ligulata, are also endemic to Panama.